Health Literacy as a Buffer: Investigating its Impact on the Relationship between Psychological Distress and Quality of Life - Mufti, Sarah; Aqsa Shahid Nadeem; Dr. Namra Shahzadi (Journal of Peace, Development and Communication, 2024)
This study aimed to investigate the relationship between health literacy, quality of life, and psychological distress in individuals with hypertension. A total of 180 hypertensive patients participated in the study, which utilized a quantitative research design. Non-probability, purposive sampling was employed, and data were gathered from both public and private hospitals, as well as the general population. Three key instruments were used: the Health Literacy Scale, the WHO Quality of Life questionnaire, and the Kessler Psychological Distress Scale (K-10), along with a demographic sheet. Demographic data were summarized with frequencies and percentages, while correlational and regression analyses explored the relationships between the key variables. The findings revealed a significant relationship (p<0.01) between health literacy, quality of life, and psychological distress. Notably, there was a strong negative correlation between health literacy and quality of life (-.336**), suggesting that higher health literacy was linked to lower quality of life. Additionally, a significant negative relationship was observed between exercise and quality of life (-.182**). Regression analysis indicated that the duration of illness was a significant predictor of health literacy, quality of life, and psychological distress.